Changes in Ghanaian farming systems: Stagnation or a quiet transformation? - Houssou, Nazaire; Johnson, Michael E.; Kolavalli, Shashidhara; Asante-Addo, Collins (International Food Policy Research Institute, 2016)
This research was designed to understand better the patterns of agricultural intensification and transformation occurring in Africa South of the Sahara using the Ghanaian case. The paper examines changes in farming systems and the role of various endogenous and exogenous factors in driving the conversion of arable lands to agricultural uses in four villages within two agroecologically distinct zones of Ghana: the Guinea Savannah and Transition zones. Using essentially historical narratives and land-cover maps supplemented with quantitative data at regional levels, the research shows that farming has intensified in the villages, while farmers have increased their farm size in response to factors such as population growth, market access, and changing rural lifestyle. The overall trend suggests a gradual move toward intensification through increasing use of labor-saving technologies rather than land-saving inputs—a pattern that contrasts with Asia’s path to its Green Revolution. The findings in this paper provide evidence of the dynamism occurring in African farming systems; hence, they point toward a departure from stagnation narratives that have come to prevail in the debate on agricultural transformation and intensification in Africa South of the Sahara. We conclude that it is essential for future research to expand the scope of this work, while policies should focus on lessons that can be learned from these historical processes of genuine change.